The leader's guide to storytelling mastering the art and discipline of business narrative - Denning, Stephen (Jossey-Bass, 2011)
"How leaders can use the right story at the right time to inspire change and action This revised and updated edition of the best-selling book A Leader's Guide to Storytelling shows how storytelling is one of the few ways to handle the most important and difficult challenges of leadership: sparking action, getting people to work together, and leading people into the future. Using myriad illustrative examples and filled with how-to techniques, this book clearly explains how you can learn to tell the right story at the right time. Stephen Denning has won awards from Financial Times, The Innovation Book Club, and 800-CEO-READ The book on leadership storytelling shows how successful leaders use stories to get their ideas across and spark enduring enthusiasm for change Stephen Denning offers a hands-on guide to unleash the power of the business narrative"--